Development and validation of the School Clinical Rugby Measure (SCRuM) test battery: understanding the qualities or skills defining good male adolescent rugby union players - Chiwaridzo, Matthew (Department of Health and Rehabilitation Sciences, 2021)
Background: Globally, the number of schoolboy adolescents playing highly competitive rugby is increasing even in countries such as Zimbabwe hardly known for dominating international rugby events. Given the increased participation rates, burgeoning talent identification and recruitment programs and the reportedly high injury risk associated with competitive youth rugby in Zimbabwe and globally, the minimal qualities or skills defining good male adolescent rugby players need further clarification. This study assembled a testing battery and compared the anthropometric variables, physiological characteristics and rugby-specific game skills of Zimbabwean schoolboys to identify qualities and/or skills discriminating elite from sub-elite male adolescent rugby players and non-rugby players within and between Under 16 (U16) and U19 age categories. Methods: This study was structured in three phases. Phase I developed the School Clinical Rugby Measure (SCRuM) test battery based on amalgamated information derived from narrative literature review, qualitative study and two systematic reviews. Using mixed methods sequential explanatory study designs, Phase II refined the test battery through the evaluation of face and logical validity using key informants (n=5) and rugby experts (n=20), respectively. Subsequently, rugby coaches (n=30) assessed the practical feasibility of implementing each SCRuM test item in the local context considering test equipment, procedural and acceptability issues. Phase III evaluated the test-retest reliability of each SCRuM test item among a sample of elite U16s (n=41) and U19s (n=41). The final study in Phase III compared cross-sectional test performances of 208 athletes from different playing standards and age category to identify SCRuM test items discriminating (i) older (U19) players from younger (U16) players regardless of playing standards, and (ii) elite from both sub-elite and nonrugby players regardless of age. Results: Phase I produced the first version of the SCRuM test battery with 23 variables. Phase II reduced the constituent components to 15 variables. The test-retest reliability study showed high intraclass correlation coefficient (ICC>0.70) for all SCRuM test items except for the 5-m, 10-m speed tests and passing-for-accuracy test. Age category had a significant main effect on all SCRuM test items except for sum of seven skinfolds (p=0.45, η2 p=0.003). Playing standard had a significant main effect ii on all variables except for height (p=0.40, η2 p=0.01) and sum of seven skinfolds (p=0.11, η2 p =0.02). Upper-and-lower body muscular strength and power, prolonged high-intensity intermittent running ability, repeated high-intensity exercise performance ability, tackling, passing and catching significantly improved with increasing playing standards. However, the Yo-Yo intermittent recovery level 1 test, vertical jump test, tackling proficiency test and running-and-catching ability skills test demonstrated greater discriminative ability across playing standards among U16s. The 40-m speed test, 2-kg medicine ball chest throw test, repeated high-intensity exercise test, one-repetition maximum bench press and back squat tests, and passing ability skills test showed better discriminative validity for differentiating U19s by playing standards. Conclusion: Irrespective of playing standard and consistent with previous studies, all SCRuM test items significantly increased with age except for skinfolds measures. These results highlight the sensitivity of component SCRuM test items in discriminating younger (U16s) from older (U19s) athletes. U16 coaches should consider these differences when designing training interventions to assist with the development of prospective U19 players. However, prolonged high-intensity intermittent running ability, lower-body muscular power, tackling proficiency and running-andcatching ability demonstrated greater discriminative ability among U16s only, indicating a possible link to higher playing standards for that age category. Upper-body muscular power, upper-and-lowerbody muscular strength, 40-m sprinting ability, repeated high-intensity exercise performance ability, and passing ability significantly improved with playing standards among U19s, highlighting the physiological characteristics and game skills capable of differentiating elite male adolescent rugby players from both sub-elite or non-rugby players at that age category. Collectively, these findings provide insight to the high school rugby coaches into the qualities and skills contextually relevant for training for the attainment of higher playing standards in schoolboy rugby at distinct age categories.